The use of model compounds to investigate the influence of fuel composition on the thermo-oxidative stability of fame/diesel blends - Vukeya, Hundzukani (Department of Chemical Engineering, 2015)
Biodiesel can be used in diesel engines without significant modification of the engine prior to use because it has properties similar to those of petroleum diesel. Biodiesel, however, exhibits lower stability compared to petroleum diesel. Small differences in fuel properties such as component concentration or total acidity can lead to the formation of deposits which can reduce engine performance and increase maintenance requirements and costs. Thermo-oxidative stressing was performed in two reactor systems in this study. For comparative purposes both sets of experiments were performed at 140Â° C. The systems used were a quartz crystal microbalance (QCM) in which oxygen was limited and open glass flasks under flowing air (unlimited oxygen). To simplify analysis, diesel model compound systems were used in which full boiling range diesel was replaced with single compounds representing the classes of compounds found in petroleum diesel. The model compounds were n-hexadecane, tetralin and decalin. Fuel analysis was performed using gas chromatography (GC) with mass spectrometric (MS) and flame ionisation (FID) detection. Further analytical methods included Fourier transform infrared (FTIR) and ultraviolet-visible (UV-Vis) spectroscopy as well as electrospray ionisation-mass spectrometry (ESI-MS).